Semantic web in higher education (Journal of Information Systems and Technology Management, 2008)
The ideas expressed in this project largely reflect the need for the satisfaction of the requirements of scientific and technical information, and generate new perspectives on a model that allows linking Directory of Scientific Publications, the Digital Libraries University and Scientific Communities with key players-users of these requirements, such as researchers, teachers and students participate in the model learning, in conjunction with the community producer of goods and services.